Optimization of milling parameters based on five-axis machining for centrifugal impeller with titanium alloy. Issue 1 (1st September 2022) - Chen, T H; Lee, J N; Tsai, M H; Shie, M J; Lin, C Y
Abstract: The centrifugal impeller is the core component of a turbojet engine. Due to its complex geometry, it is difficult to generate machining paths. Moreover, a lot of material is removed between the blades during the manufacturing process. This study investigates the optimization parameters of a titanium alloy centrifugal impeller for five-axis milling. Rough grooving toolpaths are obtained using Siemens NX software, and the NC program is obtained after post-processing conversion. VERICUT can perform cutting simulations to determine whether there is an interference or collision. During the initial cutting parameter experiment, a sensory tool holder is used to measure the tool bending moment during milling. After milling, a 3D digital microscope is used to observe the flank and face of the cutter to analyze the cutting bending moment and tool wear. Finally, the optimal cutting parameters are determined through a full-factor experiment, and the tool life parameters are verified. According to the cutting parameter experiment, the cutting depth is 1 mm, the cutting speed and feed rate is the same, and the maximum bending moment increases proportionally with depth. In addition, a tool life experiment is performed using the optimal cutting parameters: cutting speed of 50 m/min, feed rate of 250 mm/min, and cutting depth of 2 mm. The maximum cutting moment is below the wear limit of 27 Nm. The tool could cut seven grooves, and the machining time is 41 min 46 s.